APPLICATION OF BASIC CHEMICAL TEACHING METHOD BASED CAI (COMPUTER ASSISTED INSTRUCTION) USING MICROSOFT VISUAL BASIC 6.0 - Andri Hidayat; Yudi Irawan Chandra, SKom, MMSI Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2005)
This writing describes the Application-Based Method of Teaching Basic ChemicalCAI. This application consists of nine subjects that will be outlined, including theMaterial, Atomic Structure, Periodic Table, Code Name, Institute of Chemistry,Chemical equation, stoichiometry, Thermochemistry, and Gas. Each Subject SubSubject has to be explained more detail and depth about the subject selected. Inaddition this application is also accompanied by Learning Evaluation that makesusers more interactive in the learning process. Evaluation of Learning is a problem -multiple choice questions, which are summarized from nine Fundamental described.To the authors to show them in computerized form using Microsoft Visual Basic 6.0,by presenting it in the form of a computerized writer hopes this application user canbetter interact with computers and students, or users can more easily understand thelessons as well as broaden their knowledge of students about the science of chemistrythrough the application computer that is created.